CHARACTERISTICS OF BENGAL SCHOOL IN THE ART OF ARTIST SHIVKUMARI JOSHI OF MADHYA PRADESH - kumawat, Pooja; Bharadwaj, Kumkum (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The modern art in India is the result of the growth of various modern art genres in the perspective of European art. Under the British rule, when Western techniques in art were more appreciated and disseminated, a challenge arose before Indian art. Having seen adverse situations, art historian E. B. Havell has drawn the attention of the world towards rich Indian culture by glorifying it through his publications. Later, while holding the post of Principal of the Calcutta Art School, E. B. Havell came in contact with Abanindranath Tagore and their mutual cooperation in support of Indian art led to the development of Bengal School. The purpose of the presented research paper is to explore the characteristics of Bengal School in the art of artist Shivkumari Joshi of Madhya Pradesh. After introducing the Bengal School in brief, the study has been extended towards the aim of this research, for which reliable sources and artworks have been analyzed. Some images of artworks have been presented as required. On analyzing the art of Shivkumari Joshi, the characteristics of the Bengal School such as the inclusion of Indian cultures, harmony in color-scheme, attractive countenance, figures with delicate limbs, rhythm in lines, simple and clear depiction, especially the use of wash technique etc. have been observed in her artworks which have been described in detail.